The Qur'anic Counter-Narrative: A Systematic Literature Review on Deconstructing Zionist Territorial Claims and Establishing Epistemic Hegemony - Muhammad Diaz Supandi; Ihwan Agustono; Ali Mahfuz Munawar (Mauriduna : Journal of Islamic Studies, 2025)
This study critically examines the Zionist territorial claims over Palestine and offers a Qur'anic critique within the framework of epistemic counter-hegemony. Employing a Systematic Literature Review (SLR) methodology operationalized through the PRISMA protocol, this study conducted a systematic search and screening of literature from selected academic databases. The study incorporates primary sources such as the Qur'an, classical tafsir, and historical documents, alongside secondary data from academic and institutional reports. The findings reveal that Zionist claims contradict Islamic justice, which views land ownership as a divine trust, rather than an exclusive ethnic or religious right. The ecological destruction and forced displacement carried out by Zionism further violate the Islamic principles of justice and social responsibility. This study contributes to the deconstruction of the colonial Zionist narrative by suggesting an alternative model of collective sovereignty based on equality. Ultimately, the research proposes that genuine sovereignty is achieved not through territorial partition, but through cooperative stewardship of land, water, and history, grounded in the principle of tawhid, symbolizing cosmic unity.